O panelaço como resistência ao político no Brasil: discurso e memória - Damazio, Lucas Pereira (2016)
From the French Discourse Analysis. principles and its theoretical procedures, we have proposed to investigate the discursive functioning of the panelaco, occurred on March 8, 2015, Brazil. The research objectifies to analyze how the manifestation is constituted discursively into our country. For this purpose, we take into consideration that it establishes discursive relations with other historical movements, mainly the ones installed on Chile and Argentina . since other discourses mark ideologically every single discourse. Therefore, initially, as method, we did a historical study to identify relations of likenesses between these sayings, the discursive paraphrases that maintain in bases of the utterable. Then, we seek to identify the points of distances, displacements, and ruptures that existed among the panelacos, a way to comprehend the polissemic processes that were established, and the reconfigured senses about the panelaco in Brazil. In order to do so, we sought to comprise the noise functioning as a materiality of the political discourse, marking the difference between this concept for the studies of the Theories of Communication, and theoretical presuppositions of the French Discourse Analysis. With this relation, we could determine this kind of materiality was not only a noise, as point out some theorists of the field in the Theories of Communication, but a discourse of resistance that put at stake the power relations that traverse the Brazilian politics. We comprehended wherefore that this discursive materiality worked as a form of resistance; this who sought to fight, protest, and reclaim rights, simultaneously tried to silence, obliterate the sayings of the President Dilma Rousseff, as a form of refutation and mostly, empowerment.